1997
DOI: 10.1073/pnas.94.16.8658
|View full text |Cite
|
Sign up to set email alerts
|

Xeroderma pigmentosum and trichothiodystrophy are associated with different mutations in the XPD ( ERCC 2) repair/transcription gene

Abstract: The xeroderma pigmentosum group D (XPD) protein has a dual function, both in nucleotide excision repair of DNA damage and in basal transcription. Mutations in the XPD gene can result in three distinct clinical phenotypes, XP, trichothiodystrophy (TTD), and XP with Cockayne syndrome. To determine if the clinical phenotypes of XP and TTD can be attributed to the sites of the mutations, we have identified the mutations in a large group of TTD and XP-D patients. Most sites of mutations differed between XP and TTD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
220
1
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(236 citation statements)
references
References 35 publications
12
220
1
3
Order By: Relevance
“…15,21 Our XP and TTD patients had XPD mutations that are similar to those previously published. 1,5,[8][9][10][11] All of our XP and TTD patients were compound heterozygotes for two different XPD mutations. Many XP patients had the common p.R683W mutation combined with other mutations.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…15,21 Our XP and TTD patients had XPD mutations that are similar to those previously published. 1,5,[8][9][10][11] All of our XP and TTD patients were compound heterozygotes for two different XPD mutations. Many XP patients had the common p.R683W mutation combined with other mutations.…”
Section: Discussionmentioning
confidence: 86%
“…Some alleles have been considered as null, with no activity for some functions. 5 However, XPD has multiple functions and there is evidence that both XPD alleles contribute to the overall phenotype. 6 We previously reported on a patient with COFS/TTD (TTD373BE) having p.D681N and p.R616W mutations that were not in the C-terminal region but were near the common p.R683W XP-associated mutation.…”
Section: Moslehi Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…#, reference category; OR, odds ratio; CI, confidence interval.-1 Below or above the median level of 11.2 DNA adducts per 10 9 nucleotides (after exclusion of 33 subjects with adducts levels below the detection limit of the method).-2 From unconditional logistic regression analysis including in the same model all the terms in the table plus age (years), smoking history (current, ex-and never smoker), XPD-751 genotype, body mass index (kg/m 2 ), total caloric intake and intakes of vitamin C and E. different domains of XPD may affect different protein interactions, resulting in the expression of different phenotypes. 36 We studied the same XPD-Lys751Gln polymorphism: this might have divergent effects in different DNA repair pathways, or other types of DNA damage, when compared to hydrophobic bulky DNA adducts we have measured. Another recent study, of relatively small size, found no effect of XPD, but some association between XRCC1 genotype and polyphenol DNA adducts.…”
Section: Multivariate Analysismentioning
confidence: 99%